Varying patterns of brachial artery flow‐mediated dilatation in women with polycystic ovary syndrome and controls: An application of the group‐based trajectory modeling. Issue 1 (14th July 2015) - Meyer, Michelle L.; Tepper, Ping G.; Barinas‐Mitchell, Emma; Korytkowski, Mary T.; Talbott, Evelyn O.
ABSTRACT: Purpose: To identify changing patterns of absolute change in brachial artery lumen diameter (LD) after reactive hyperemia in women with polycystic ovary syndrome (PCOS) and controls and to quantify the association of PCOS status and participants' factors with these patterns. Methods: Brachial flow‐mediated dilation was measured in 128 women with PCOS and 148 controls aged 30–60 years. Group‐based trajectory modeling was used to investigate absolute change in LD every 30 seconds for 2 minutes after occluding cuff deflation. Multinomial logistic regression was used to identify factors associated with trajectories. Results: Three patterns emerged, namely nondilators (42.2%), dilators (44.6%), and enhanced dilators (13.0%). The proportion of women with PCOS did not differ across groups. Independently of age and PCOS status, larger baseline LD (odds ratio; 95% confidence interval: 2.51; 1.29, 4.89) and lower insulin levels (0.70; 0.52, 0.93) were associated with nondilators rather than with dilators. Higher total cholesterol was associated with dilators in women with PCOS but with nondilators in controls. Conclusions: Trajectory modeling identified distinct patterns of change in LD and factors associated with the endothelial response. This method may be a useful tool to understand the brachial flow‐mediated vasodilator response. © 2015 Wiley Periodicals, Inc. J Clin Ultrasound 44 :46–54, 2016